2019
DOI: 10.3389/fmicb.2019.00485
|View full text |Cite
|
Sign up to set email alerts
|

Clonally Diverse Methicillin and Multidrug Resistant Coagulase Negative Staphylococci Are Ubiquitous and Pose Transfer Ability Between Pets and Their Owners

Abstract: Sixty-eight owners and 66 pets, from 43 unrelated pet-owning households were screened for methicillin-resistant coagulase negative staphylococci (MRCoNS), potential cases of MRCoNS interspecies transmission (IT), and persistence. MRCoNS isolates were identified by microbiological and molecular tests. MLST-based phylogenetic analysis was performed in Staphylococcus epidermidis isolates. Antimicrobial susceptibility was evaluated using phenotypic and molecular methods. SCC mec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 63 publications
3
36
2
Order By: Relevance
“…However, higher MRCoNS prevalence figures of 86% [ 12 ] and 100% [ 13 ] were detected for CoNS implicated in infections in South Africa. The S. epidermidis group ( S. epidermidis and S. haemolyticus ) is an important cause of nosocomial infections [ 1 ]. S. epidermidis is the most frequently isolated staphylococcal species in humans and considered the most important CoNS species [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, higher MRCoNS prevalence figures of 86% [ 12 ] and 100% [ 13 ] were detected for CoNS implicated in infections in South Africa. The S. epidermidis group ( S. epidermidis and S. haemolyticus ) is an important cause of nosocomial infections [ 1 ]. S. epidermidis is the most frequently isolated staphylococcal species in humans and considered the most important CoNS species [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococci are classified as either coagulase-positive or coagulase-negative, depending on their ability to clot plasma that is facilitated by the enzyme coagulase [ 1 ]. Coagulase-negative staphylococci (CoNS) are the most frequent colonizers of the skin and mucous membranes and the most frequently isolated organisms in microbiology laboratories [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies demonstrated that infections caused by these species affect debilitated domestic animals as cats with conjunctivitis, upper respiratory tract and skin or wound infections [16], or dogs with keratitis or urinary tract infections [17,18]. This is especially concerning, since it was already demonstrated that CoNS may be transferred from pets to their owners [19,20]. Moreover, some farm animals such as chickens are known to be the main reservoirs of antimicrobial resistance genes [21].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the molecular characteristics of CoNS isolated from food items, companion animals, livestock and clinical samples [ 1 , 5 , 8 , 13 , 14 , 15 , 16 , 17 ], but CoNS from wildlife remains largely unattended. In this regard, birds have been postulated as sentinels, reservoirs and potential disseminators of antimicrobial resistance due to their interaction with the human interface, their diverse ecological niches and their capacity to migrate long distances [ 18 ].…”
Section: Introductionmentioning
confidence: 99%